Giant cell arteritis: a closer look at its ophthalmological manifestations - Pinto Ferreira, Nuno G (BMJ Case Rep, 2015)
Giant cell arteritis with ocular involvement is an ocular emergency. Arteritic anterior ischaemic optic neuropathy (AAION) is the most common ophthalmological manifestation associated with this disease. Visual loss is usually permanent with rare cases showing visual recovery. Visual improvement, if it occurs, is generally limited, and the visual field defects are persistent and severe. The main goal of AAION treatment is the preservation of vision in the fellow eye. In patients with neurophthalmological manifestations, high-dose corticosteroids should be initiated immediately and aggressively, and maintained thereafter. We present a case of AAION and severe vision loss where significant visual recovery was seen after treatment.